(untitled) (Majalah Kedokteran Bandung, 2019)
An increase in the incidence of diabetes mellitus type 2 (DM-2) has been observed from 1.1% in 2007 to 1.5% in 2018 with incidents occur in both urban areas and rural areas of Indonesia. Garut as one of the rural areas in Indonesia is the fourth district with the highest DM-2 incidence in West Java Province, Idnonesia. Physical activity is considered to affect the glycemic control and weight loss in DM-2 patients. Therefore, the purpose of this study was to determine the relation between the physical activity level and blood glucose level in DM-2 patients in Garut, Indonesia. This was a cross-sectional observational analytic study on 46 DM-2 patients who were the members of the Garut Branch of the Indonesian Diabetes Association (PERSADIA), in May 2018. The physical activity level was measured using the International Physical Activity Questionnaire (IPAQ) while the blood glucose level was measured using fasting blood glucose level test. Data were then analyzed using analysis of variance test. Results showed that most participants had a low level of physical activity (52.2%) while the lowest fasting blood glucose was obtained from patients with high physical activity (98.63±11.6), compared to those with moderate and low physical activity levels (123.43±20.16 and 164.21±19.04 mg/dL, respectively) with p=0.000 (p<0.05). Lifestyle changes, especially in the form of the lack physical activity, were seen alsonin the rural area in Indonesia. High physical activity level is the most effective measure to lower fasting blood glucose level in DM-2 patients. Aktivitas Fisik Menurunkan Kadar Glukosa Darah Puasa pada Pasien Diabetes Mellitus Tipe 2: Menggunakan the International Physical Activity Questionnaire (IPAQ) di Rural Area Kejadian pasien diabetes mellitus tipe 2 (DM-2) pada tahun 2018 (1,5%) mengalami peningkatan dibandingkan tahun 2007 (1,1%), terjadi baik di daerah perkotaan dan pedesaan di Indonesia. Garut sebagai salah satu daerah pedesaan di Indonesia adalah salah satu kabupaten dengan insidens DM-2 terbesar keempat di Jawa Barat-Indonesia. Aktivitas fisik dianggap memengaruhi kontrol glikemik dan penurunan berat badan pada pasien DM-2. Oleh karena itu, tujuan dari penelitian ini adalah mengetahui hubungan tingkat aktivitas fisik dengan kadar glukosa darah pada pasien DM-2 di Garut-Indonesia. Subjek penelitian ini adalah 46 pasien DM-2 yang tergabung dalam Persatuan Diabetes Indonesia (PERSADIA), cabang Kabupaten Garut, pada Mei 2018. Metode penelitian yang digunakan adalah analitik observasional dengan metode cross-sectional. International Physical Activity Questionnaire (IPAQ) sebagai alat untuk mengukur tingkat aktivitas fisik, selain itu dilakukan pengukuran kadar glukosa darah puasa. Data dianalisis menggunakan analysis of variance test. Hasil penelitian menunjukkan bahwa sebagian besar peserta memiliki tingkat aktivitas fisik yang rendah (52,2%) dan glukosa darah puasa terendah diperoleh dari pasien dengan aktivitas fisik yang tinggi (98,63±11,6) dibandingkan dengan aktivitas fisik sedang dan rendah (123,43±20,16 dan 164,21±19,04 mg/dL), dengan p=0.000 (p<0,05). Perubahan gaya hidup terutama kurangnya aktivitas fisik juga terjadi di daerah pedesaan di Indonesia dan aktivitas fisik yang tinggi adalah tipe yang paling efektif menurunkan kadar glukosa darah puasa pada pasien DM-2.